External visual interface for a Nikon 6D autocollimator - Bergues, Guillermo (2014)
Ponencia presentada en IEEE I&M International Instrumentation and Measurement Thechnology Conference, 12 al 15 de mayo de 2014, Montevideo, Uruguay.